The potential, strategies, and challenges of Monascus pigment for food application - Egea, Mariana Buranelo; Dantas, Luciana Arantes; Sousa, Tainara Leal de; Lima, Alan Gomes; Lemes, Ailton Cesar (Frontiers in Sustainable Food Systems, 2023)
Pigments are used to provide color in the food production process, greater attractiveness, and acceptability, compensate the color loss in food that occurred by industrial processing and storage, determine the identity of certain products, standardize or intensify color, as well as provide color to foods originally colorless, among others. The demand for natural pigments for application in the food industry has been continuously increasing in substitution for synthetic pigments by hypersensitivity, carcinogenesis, and negative environmental impacts. Natural pigments are colored substances derived from natural sources, that have lower time of biodegradability, greater compatibility with the environment, and fewer adverse health effects compared with synthetic pigments. In this sense, great focus has been given to the biotechnological potential of species of Monascus sp. to produce red, orange, and yellow pigments using different types of the fermentation process (submerged or in solid-state fermentation), substrates (synthetic, natural, and by-products) and process parameters (temperature, pH, agitation, aeration, etc.), aiming at optimizing and reducing costs in pigment production. In this sense, this mini-review presents the trend of production and applying Monascus pigment in foods, as well as its strategies and challenges.